2005
DOI: 10.1038/sj.cdd.4401560
|View full text |Cite
|
Sign up to set email alerts
|

Motoneuronal death during spinal cord development is mediated by oxidative stress

Abstract: The involvement of reactive oxygen species (ROS) in neuronal death has been determined in culture, and in association with several neurodegenerative disorders. We examined whether ROS participate in the cell death observed during spinal cord development. We found that the general pattern of high ROS levels, gene expression for some antioxidant enzymes, and motoneuron death correlated positively along spinal cord development. ROS were reduced in spinal cords cultured in the presence of a synthetic superoxide di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…7a,b). Motor neuron numbers also declined in wild type embryos due to pruning, which has been linked to oxidative stress exposure 13 . NeuN staining to detect all neurons showed that the observed reduction in neuronal numbers was due to the loss of ChAT + motor neurons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7a,b). Motor neuron numbers also declined in wild type embryos due to pruning, which has been linked to oxidative stress exposure 13 . NeuN staining to detect all neurons showed that the observed reduction in neuronal numbers was due to the loss of ChAT + motor neurons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include mitochondria, the Golgi apparatus, rough endoplasmic reticulum, neuromuscular synapses, MN axons. The neuron's response to oxidative stress, ER stress, or alterations in proteasome function may manifest in these pathological changes (Sánchez-Carbente et al 2005; Fischer and Glass 2007; Boillée and Cleveland 2008; Cheroni et al 2009). Physiological changes such as alterations in anterograde and retrograde axonal transport and hyperexcitotoxicity are also reported to occur.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ROS can accumulate in response to programmed cell death, injury, excitotoxicity, glucose deprivation, and neurodegenerative diseases including Spinal Muscular Atrophy (SMA), Amyotrophic Lateral Sclerosis (ALS), Alzheimer's disease (AD), and Parkinson's disease (PD). (Andrus et al, 1998;Hayashi et al, 2002;Liu et al, 2003;Rego and Oliveira, 2003;Bruijn et al, 2004;Parihar and Hemnani, 2004;Zhang et al, 2004;Sanchez-Carbente et al, 2005;Xu et al, 2005;Pasinelli and Brown, 2006). These ROS, including superoxide, peroxinitrite, and hydroxyl radical exert their effects through the oxidative modification of lipid, protein, and DNA (Sayre et al, 2001).…”
Section: Introductionmentioning
confidence: 96%